Populorum Progressio's Vision in an Unequal World: A Theological Ethical Evaluation From the Global South - Raymond Aina (Journal of Moral Theology, 2017)
Who is listening to Populorum Progressio today where the global economy serves just 1% of the world’s population and neglects much of the Global South? This essay investigates this question in four parts. First, this essay summarizes Populorum Progressio’s statement of the economic problem facing the world and, second, Paul VI’s responsibility ethics as a response to this problem. Third, the essay traces how subsequent encyclicals shifted Populorum Progressio’s emphasis on solidarity as a principle of justice resulting in structural change to a virtue that guides personal change. The final section indicates how Populorum Progressio’s emphasis on solidarity as work of justice can help the Global South—using the example of Nigeria.